Cerebral Arterial Thrombosis in a Child with Nephrotic Syndrome - Kara, A.; Gurgoze, M. K.; Serin, H. M.; Aydin, M. (Wolters Kluwer Medknow Publications, 2018)
Nephrotic syndrome (NS) in childhood may be associated with thromboembolic complications, mainly in venous origin. However, arterial thrombosis may also be seen as a very rare and life-threatening complication. Herein, we described a case of steroid-resistant NS who did not respond to full-dose steroid treatment for 8 weeks and was complicated by neurological findings. The renal biopsy was consistent with focal segmental glomerulosclerosis. His cerebral magnetic resonance angiography showed the sudden termination of M3 branch of the left middle cerebral artery which corresponded with subacute infarction in the left frontoparietotemporal area. Thrombosis panel yielded the results of hyperhomocysteinemia (46.1 mu mol/ L, range: 5-15 mu mol/ L) and heterozygous methylene tetrahydrofolate reductase mutation (C677T, A1298C). After that, the patient was given medical therapy including anticoagulant treatment. Improvement in the neurological outcome was determined on the 1st month of follow-up examinations.
Keywords: Arterial thrombosis; cerebral infarction; children; nephrotic syndrome; treatment